A Critical Note on the Definition of Related Goods - Ichimura, S. (Review of Economic Studies, 1950)
Journal Article A Critical Note on the Definition of Related Goods Get access S. Ichimura S. Ichimura New York Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 18, Issue 3, 1950, Pages 179–183, https://doi.org/10.2307/2295977 Published: 01 September 1950